A coumarin lignanoid from the stems of Kadsura heteroclita. Issue 7 (1st April 2015) - Su, Wei; Zhao, Jianping; Yang, Min; Yan, Hui-Wen; Pang, Tao; Chen, Sheng-Huang; Huang, Hui-Yong; Zhang, Shui-Han; Ma, Xiao-Chi; Guo, De-An; Khan, Ikhlas A.; Wang, Wei
Graphical abstract: Abstract: Coumarinlignan (1 ), possessing a unique coumarin-containing lignan skeleton, was isolated from the stems of Kadsura heteroclita . Its structure and absolute configuration were determined by spectroscopic techniques, especially 2D NMR and X-ray crystallographic data analyses. The proposed biosynthetic pathway is discussed. This new compound showed good anti-HBV activity against HBeAg and HBsAg, and moderate anti-fibrotic and neuroprotective activities.